Development of mobile application prototype for building inspection work - Hasnan Hashim,; Adi Irfan Che Ani,; Kharizam Ismail,; Rafidah Abd Karim,; Alia Abdullah Saleh,; Suhana Johar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Building surveyors traditionally relied on descriptive longhand surveys to record an information by hand during on-site building inspections. However, the traditional approach such as checklist that usually practiced were unstructured and unstandardized among organization. In certain cases, it might have a missing document and issue on time-consuming for analysis. Therefore, this mobile application prototype purposely built to track the building defects where it can be used on site during building inspection. This is to record the information according to 11 evaluation criteria namely defect classification, type of building, type of location, type of element, sub-element, causes of defects, defects categories, defect groups, type of defects, building condition level and priority level of repairs. Besides that, the pictures or images can also be kept as supporting evidence. This mobile application prototype included three development phases which are design and utilization, system installation and maintenance and implementation. This mobile application has been projected to be used with mobile devices such as tablets or smartphones. It can also be accessed either through Play Store (for Android User) or the App Store (for Apple’s iOS user). This mobile application also provides a convenient and alternative method in recording the real time findings instead of using manual checklist. Finally, it has the potential to be developed and commercialized with the addition of more user-friendly features.